RECOVERY OF USED VEGETABLE OIL BY PROGRESSIVE FREEZING FOR RECYCLING AND REUSE - CHANDRA SEGARAN, RUBINI (IRC, 2019)
Improper waste management of used vegetable oil leads to discharge of used vegetable oil to the environment and this will cause environmental pollution particularly land and water pollution. In water, oil layer covers the surface and prevents the dissolution of oxygen, thus causing destroys aquatic life in the marine environment. This research aims to study to recover the used vegetable oil by progressive freezing for recycling and reuse so that the volume of used vegetable oil that being disposed into river can be reduced in order to lessen the negative impact on environmental and health aspects. This progressive freezing method is beneficiary as it easier and simpler to separate the ice crystal from the mother solution, since there is only one large block of ice crystal, resulting in low maintenance cost. The purity of progressive freezing produced ice crystals is high. As for progressive freezing, three operating parameters which are coolant temperature ranging from 2°C to 5°C, stirring rate ranging from 50 rpm to 200 rpm and freezing time from 30 to 60 minutes have been studied to evaluate the percentage of recovery and the quality of used vegetable oil after recovery.